Fabrication of GaAs micro-optical components using wet etching assisted femtosecond laser ablation. Issue 20 (27th November 2020) - Sun, Xiaoyan; Zhou, Fang; Dong, Xinran; Zhang, Fan; Liang, Chang; Duan, Lian; Hu, Youwang; Duan, Ji'an
Abstract : Femtosecond laser ablation is a flexible method for manufacturing gallium arsenide (GaAs) micro-optical components. However, its machining efficiency and surface quality do not satisfy industry requirements. Wet etching assisted femtosecond laser ablation is proposed to solve these problems. After corrosion, protrusions and particles are selectively corroded. X-ray diffraction and energy dispersive X-ray spectroscopy results show that oxides are formed after laser ablation, and the crystal cell size of GaAs increases. Thus the contact area between hydrofluoric acid atoms and the GaAs crystal cell increases, the ratio of modified-to-unmodified corrosion rate is as high as 10:1. A one-dimensional grating, a conventional Fresnel zone plate (FZP), and a fractal FZP are fabricated using this method. Experiments show that the GaAs micro-optical component can diffract and focus infrared light with a wavelength of 1.5 µm well. The process offers a way to achieve high efficiency and quality manufacturing of GaAs microstructures.